KEANEKARAGAMAN MAKROFAUNA TANAH PADA LUBANG RESAPAN BIOPORI YANG DIISI MEDIA LIMBAH KULIT BUAH KAKAO (Theobroma cacao L.) - Nurhayati Nurhayati; Fahri Fahri; Annawaty Annawaty (Biology Department, Mathematics and natural science, Tadulako University, 2017)
The objective of this study is to determine the diversity of the soil macrofauna in Biopore Absoption Holes filled with cocoa pod waste (Theobroma cacaoL.). The study was conducted from April to August 2015 in the cocoa plantations Sibonu Village, Sigi District, Central Sulawesi. Sample identification executed in laboratory of Biology, Faculty of Basic Sciences,Tadulako University. The method used in this study are handsorting. There are six species identified from the field i.e: scorpion (Mastigoproctus giganteus), spiders (FamilyLycosidae), red small-millipedes (Order Spirobolida) and black small-millipedes (Order Pselaphognatha), legthousand yellow (ClassDiplopoda) and earthworms (class Oligochaeta). Diversity and even ness indexes are low.